THE SYSTEM OF COLLECTING ENVIRONMENTAL INFORMATION ON THE STATE OF THE TERRITORIAL TECHNOSPHERE - Oleg Stanislavovich Vinogradov (Science and Innovation Center Publishing House, 2018)
The ecological and economic condition of cities and agricultural lands is decisive for the further development of territories. Global environmental problems associated with the increase in economic damage from natural and man-made disasters, pollution of the air and water environment, and soil affect the interests of the Russian Federation and its citizens. The ecological situation in the Russian Federation is characterized by a high level of anthropogenic impact on the environment and humans, and this is due not only to the consequences of the past economic crisis in our country, but also to the economic conditions applied in industry and agriculture. For the effective functioning of the system of integrated monitoring of the state of the territorial technosphere, it is extremely important to scientifically-based formation of a network of monitoring stations, that is, locations and methods of sensor placement. The article contains a general scheme for collecting and transmitting information on the results of monitoring, in accordance with which groups of fixed and mobile sensors are selected and described. Sensors are used to automatically measure and record the volume and mass of emissions, discharges, and concentrations of pollutants in air, water, and soil. Timely determination of the fact that the maximum permissible values measured by the sensors are exceeded will be able to prevent the development of an emergency situation and preserve the life and health of the population, as well as reduce the economic costs of the subsequent reclamation of the affected areas.